Evaluation of CHP for Electricity and Drying of Agricultural Products in a Nigerian Rural Community. (May 2017) - Lamidi, Rasaq O.; Wang, Yao Dong; Pathare, Pankaj B.; Roskily, A.P.
Abstract: The techno-economic performance analysis of biogas production, power generation and recovery of heat for drying of agricultural products for a Nigerian rural community is explored through process simulation. In this work, biogas generation from a 10.33MT/day cattle market waste was fed into a 72kWe CAT internal combustion engine and the model has been developed using Aspen HYSYS R process simulator. Simulation results shows that about 191.63MT per annum of tomato can be dried with the recovered heat while heat recovery for anaerobic digestion and drying of agricultural products increases the system's heat efficiency from 25.6% to 58.4%. The results also show that, with the current electricity tariffs for remote areas being charged at USD 0.02/kWh and Feed-in Tariffs (FITs), NPV is positive and the payback period is 3.2 years. However, system less than 1MW is not currently captured in Nigeria's FITs system while the economic indices are negative without FITs. Effects of interest rate regimes on economic indices is also explored as such system could be farm based and entitled to loan from the Nigerian Agricultural Development Bank, Bank of Industry and Commercial banks with interest rates 7%, 9% and 20% respectively. The results presented in this paper increased research knowledge on application of biogas CHP in Nigerian rural communities especially on integration of energy generation with processing of agricultural products